The impact of taxation and corporate governance on dividend policy: a case of listed firms on the ghana stock exchange - AWUGYE JOHN (KNUST, 2024)
A thesis submitted to the department of accounting and finance college of humanities and social sciences in partial fulfilment of the requirements for the degree of msc. Accounting and finance